Peningkatan Pengetahuan dan Pelatihan Pencegahan Low Back Pain pada Lansia - Muliartini Ni Luh Putu; Udayani Nesa (Warmadewa University Press, 2023)
One of the musculoskeletal complaints is Low back pain (LBP) or pain in the lower back that becomes epidemic, complained about 80% of the public, at least this complaint is felt once in his life. The elderly population according to the WHO category over 60 years old is a potential community group to experience LBP complaints in their daily lives, so that understandable efforts and assistance are needed in the elderly group, creating a physical and non-physical condition in reducing the incidence and complaints of LBP so as to improve the quality of life and welfare. The purpose of this community partnership program is to assist government programs in improving the quality of life of the community with active learning methods to increase knowledge of LBP symptoms, prevention and daily behaviors that can prevent and reduce LBP complaints implemented at Tabanan Hospital then assistance and visits to monitor complaints and provide assistance in the form of LBP corsets and supplements. The results obtained are increasing knowledge and changes in daily behavior so as to reduce complaints of LBP